Mussolini Visits Hitler (IHF, 1937)
Duration: 00:30:00 When Benito Mussolini visited Adolf Hitler in September 1937, a million people jammed Berlin's Olympic Stadium and adjoining Mayfield to hear speeches and witness a spectacular military exercise. This original Nazi propaganda film also features scenes of Mussolini meeting with Nazi leaders in Munich, watching the German Army's field maneuvers, visiting Göring and reviewing military parades.